Pengaruh Model Problem Based Introduction (PBI) terhadap Prestasi Belajar IPS Kompetensi Mengenal Jenis-Jenis Usaha dan Kegiatan Ekonomi di Indonesia - Nursyamsiah Nursyamsiah (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2017)
This study aims to find out student learning outcomes through the application of PBI Model in IPS learning, knowing student activity through the application of Problem Based Introduction Model in IPS learning. This research was conducted in the form of Classroom Action Research. The stages are: Action Planning, Action Implementation, Evaluation / Observation and Reflection. The subjects of this study are students of class V semester 1 year lesson 2013/2014 as many as 24 people. The research data are: (1). Student learning outcomes are collected through a learning result test. (2). Student activity is collected through observation guidelines. Data were analyzed descriptively qualitative. From result of data analysis found that: (1). Average student learning outcomes 70.77 Classical completeness 83.33% (2). Student activity in following learning increases at every meeting. Based on the above data, the application of PBI model can be used as one of the strategies in the learning process.